용인시 농축산물 종합유통센터 설치 타당성 검토 - 김병률 (한국농촌경제연구원, 2005)
In Korea, there are diverse distribution channels of agricultural products from farm to consumers. Historically, the role of agricultural wholesale markets which are spreaded out across whole country has carried out vast important function on the viewpoints of market efficiency and lucent product distribution over twenty five years. However, since 1994, new type of Marketing however, there is no agricultural wholesale market at all. Thus, we assessed the expected scale of the proposed Marketing & Distribution Center of Agricultural Product focusing on whether it will contribute to the welfare of both producers and consumers in Yong-In City. Also there exists some risks to manage new & huge facility on the several matters. Based on the additional study such as current problems and issues of pre-existing other Marketing & Distribution Center of Agricultural Product, we proposed what Yong-In City should care about, and what they should prepare from the begining.